x+16(x-1)=7(3+x)

Simple and best practice solution for x+16(x-1)=7(3+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+16(x-1)=7(3+x) equation:


Simplifying
x + 16(x + -1) = 7(3 + x)

Reorder the terms:
x + 16(-1 + x) = 7(3 + x)
x + (-1 * 16 + x * 16) = 7(3 + x)
x + (-16 + 16x) = 7(3 + x)

Reorder the terms:
-16 + x + 16x = 7(3 + x)

Combine like terms: x + 16x = 17x
-16 + 17x = 7(3 + x)
-16 + 17x = (3 * 7 + x * 7)
-16 + 17x = (21 + 7x)

Solving
-16 + 17x = 21 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-16 + 17x + -7x = 21 + 7x + -7x

Combine like terms: 17x + -7x = 10x
-16 + 10x = 21 + 7x + -7x

Combine like terms: 7x + -7x = 0
-16 + 10x = 21 + 0
-16 + 10x = 21

Add '16' to each side of the equation.
-16 + 16 + 10x = 21 + 16

Combine like terms: -16 + 16 = 0
0 + 10x = 21 + 16
10x = 21 + 16

Combine like terms: 21 + 16 = 37
10x = 37

Divide each side by '10'.
x = 3.7

Simplifying
x = 3.7

See similar equations:

| 3+m=29 | | (2w^2+2w)+(9w^2+4w+3)= | | 5(x-3)+2k=41 | | 27+5s=189 | | (2w^2+2w)+(9w^3+4w+3)= | | -10x-10+3x=18 | | 39x+2=158 | | -2(8+2x)=-28 | | 4+8x=126 | | y-20=-42 | | 5x=8-12x+6 | | 25x+15=90 | | -5-3x=10 | | 3y+5=41 | | 2x-9+3x=9-x | | 103-1x+2x=6x-7 | | 1y=6-4y | | 12+6x=84 | | 8u/4+u=13 | | 2x+8=2x-3 | | (9-m)+4m+6= | | 3t^2+2+8t+3=0 | | 14x+8x+4=180 | | 0.2x+3.4+0.8=4 | | 4p^2+12+9=0 | | -5r+2r=-18 | | x^2+2=4x+6 | | 2x+x+14+x-38=180 | | 6t^2+2t-20= | | -6p^2=-510 | | y-83=3y-23 | | 8x-7=8(x-2) |

Equations solver categories